Agency and clientship in public encounters: co‐constructing 'neediness' and 'worthiness' in shelter placement meetings. (9th January 2019) - Mik‐Meyer, Nanna; Silverman, David
Abstract: This article seeks to develop our understanding of the agency of vulnerable groups who at first sight may not seem to have much agency in their lives. It explores the co‐constructed nature of agency in three Danish homeless shelters. Unlike earlier interview‐based studies, our research is based on naturalistic data drawn from 23 video‐recorded placement meetings. Using concepts from Goffman, we examine how versions of the neediness and worthiness of homeless people are negotiated verbally and bodily between staff and clients. We find that homeless people have to juggle two partly contradictory roles when they are given or take the roles of either a (active) citizen or a (passive) client. Clientship is actively negotiated by both parties and demonstrates the agency of homeless people: they can collaborate with (as clients) or challenge (as citizens) the staff's attempts to formulate solutions to their troubles. We further examine how the professional ideology of client centredness affects the meeting between the two parties. However, we show that, like any discourse, client centredness has no intrinsic meaning and is played out by actors in very different ways. In work with the homeless, the discourse of client centredness is related to discourses of 'neediness', 'worthiness' and 'value for money' that define agency in different ways and make three different client positions available: the resolute client, the acquiescent client and the passive client.